Factors Influencing Stunting in Children Toddlers in the Working Area of the Puskesmas Kutambaru in 2023 - Hasanah, Hijratul; Efendy, Ismail; Nasution, Ramadhani Syafitri (Universitas Ibn Khaldun Bogor, 2024)
Background: Stunting is one of the targets of the Sustainable Development Goals (SDGs) which is included in Goal 2, namely to end hunger and various forms of malnutrition by 2030 and achieve food security. The target set is to reduce the stunting rate by 40% by 2025. Stunting is caused by prolonged (chronic) malnutrition and repeated infections. Objective: The aim of this research is to determine and analyze the factors that influence stunting in toddlers in the Kutambaru Health Center working area in 2023. Methodology: This research uses quantitative methods with a cross sectional design and sampling using random sampling. The research population was 297 respondents and the research sample was 75 mothers who had stunted toddlers. This research uses a questionnaire. The research time is December 2023. This research analysis uses Univariate, Bivariate and Multivariate. The statistical tests used are the chi-square test and multiple logistic regression with the Enter method. Results: Research results regarding influencemother's height pvalue= 0.004,birth height pvalue= 0.003,birth weightpvalue= 0.002,Exclusive Breastfeeding pvalue= 0.001, History of infectious disease pvalue= 0.001, and immunization status pvalue= 0.002with Stunting in toddlers. Based on the results of the multiple logistic regression test, the variable that is very influential is Exclusive Breast Milk with an Exp(B) value of 14,594. Conclusion:The conclusion in this study is that there is an influence of maternal height, birth height, birth weight, exclusive breastfeeding, history of infectious disease and immunization status with Stunting.in toddlers in the Kutambaru Community Health Center working area.To be able to reduce the prevalence of stunting in toddlersIt is hoped that cooperation from the Health Service, Community Health Centers, especially health workersto be able to increase health promotion about stunting, the benefits of exclusive breastfeeding, the risk of infectious diseases and the benefits of immunization for children routinely every month.